It’s complex: reframing narratives around the social impacts of mine closure - O.'Keefe, E. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mining leaves communities better off: this is something the mining industry is committed to. However, the evidence base for the positive impacts of mining on communities enduring after closure is surprisingly thin. This also means an evidence-based approach to taking action on the social aspects of mine closure is similarly limited. Since the late 1990s the mining industry’s approach to social impacts has been framed by a narrative that mining has the potential for positive social impacts, that mining companies have responsibility for managing these impacts and that this can be achieved through the integration of company management systems. This study reviews a wide range of mine closure cases to identify common typologies and patterns in how mining leaves communities, including the role of mining companies in this process. The study identifies negative, positive and more benign exemplars of the social aspects of mine closure. However, no example was identified which clearly demonstrated the ideal model of a community being left better off after mining as a result of planned pre-closure mining company activities, and the potential reasons for this are outlined. The need for an alternative exemplar of former mining communities is investigated, as well as some of the initiatives underway in these contexts. The case studies highlight the complex nature of the systems in which many mines close and the ‘wicked problem’ of socio-economic transitions linked to mine closure. As such, there is a need to reframe narratives and further promote and adopt approaches which are better suited to the challenging complexity associated with former mining communities.